Gonad pathology, sex hormone modulation and vitellogenin expression in Chrysichthys nigrodigitatus from Lagos and Epe lagoons within the southern-lagoon system, Nigeria - Akangbe, Olusola A.; Chukwuka, Azubuike V.; Imiuwa, Maurice E.; Adeogun, Aina O. (Frontiers in Toxicology, 2024)
The ubiquity of estrogenic chemicals in aquatic environments has been implicated in adverse effects on fish reproductive health and success with vitellogenin protein levels in blood serum of male fish considered an important biomarker to detect fish exposure to xenoestrogens. However current knowledge on estrogenic effects in tropical environments span limited number of fish species; thus, this study aimed to investigate the impact of environmental estrogens on the reproductive health of Chrysichthys nigrodigitatus in effluentreceiving areas of Lagos and Epe lagoons. A total of 195 fish samples were analyzed for vitellogenin protein, sex hormones (testosterone and 17 β-estradiol) and gonad pathology. The results showed varying degrees of gonadal alterations in male and female fish, including empty seminiferous tubules and distorted ovaries, with intersex observed in 3.81% of Lagos and 3.33% of Epe. Testosterone levels were generally higher in females and males from both lagoons, while E2 levels were higher in females from both lagoons, with Lagos showing higher levels than Epe. Vtg levels were higher in males than females in Lagos samples but showed no significant difference in Epe samples. While analysis of contaminants revealed that metals (Hg, As, and Cr), phthalates (DEHP, DBP, and DEP) in both sexes in the Epe population showed similar trends, multivariate depictions from the PCA revealed sex-specific patterns of metal uptake (Cd) in male fishes at the Lagos Lagoon. The positive association between higher loadings of pH and higher metal and DBP levels in sediment at the Lagos lagoon, suggests the influence of higher alkalinity in lower bioavailability of these contaminants. Our results suggest endocrine disrupting effects in male and female Chrysichthys nigrodigitatus in Lagos and Epe lagoons population, with marked differences in hormone and contaminant concentrations between the two lagoon systems. These indicate that identification of specific contaminants and their spatial and temporal trends can help inform targeted management and remediation efforts to protect and restore these valuable aquatic ecosystems.